Online brand awareness: determining the relative importance of Facebook and other strategies among the Malaysian consumers - Haque, A. K. M. Ahasanul; Momen, Abdul; Sultana, Seyama; Yasmin, Farzana (International Foundation for Research and Development, 2013)
The purpose of this study is to determine the relative importance of Facebook with other strategies like affiliate marketing and word of mouth in creating online brand awareness. Both exploratory and confirmatory factor analysis is used in the study. The study chooses 303 Malaysian frequent internet users as the respondents. In confirmatory factor analysis, a structural equation modelling (SEM) approach is applied to determine the relationship among the exogenous and endogenous constructs. The study finds facebook as the most influential online brand awareness creating strategies followed by the affiliated marketing and online word of mouth. In creating the online brand awareness; all the strategies have positive influence, however. The study can be a useful guideline for managerial implication in practice